Види, джерела й способи отримання інформації для оцінки оперативної обстановки в кримінально-виконавчій установі - Копотун, І.; Kopotun, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено види, джерела й способи отримання інформації для оцінки оперативної обстановки в кримінально-виконавчих установах. Обґрунтовано класифікацію оперативної інформації на види за змістом та наслідками, серед яких основними є інформація про: 1) зміни, що відбуваються в кількісному складі засуд- жених; 2) криміногенну характеристику засуджених; 3) кримінальну ситуацію у виправній колонії; 4) вилучені предмети; 5) міжособистісні конфлікти в середовищі засуджених. Володіння такими даними дає змогу прогнозувати криміногенну ситуацію в середовищі засуджених.The article is devoted to the study of species, sources and methods of obtaining information to assess the operational situation in the penal institutions. Such kinds of information are justified: 1) changes in the quantitative composition of the convicts; 2) the criminogenic characteristics of conwicts associated with their propensity to illegal behavior; 3) the crime situation in the penal institution; 4) the analysis of violations of the established order of a sentence; 5) the specification of the measures applied to convicted for violation of the order of a sentence; 6) types and number of impounded prohibited items, the exsistance and the nature of interpersonal conflicts among the convicts; advanced analysis of the criminal situation between convicted, complications of the operational situation.
Types, Sources, and Methods of Obtaining Information Toassess Operational Situation in Penitentiary Institutions.
Keywords: оперативна обстановка; кримінально-виконавчі установи; криміногенна ситуація.; operational situation; penitentiary institutions; crime situation.